INTERNATIONAL TRAFFIC OF NARCOTICS - NICOLETA-ELENA BUZATU (Challenges of the Knowledge Society)
The present essay tries to analyze the infringement referring to the international traffic of narcotics, an infringement regulated, together with other infringements regarding the traffic of narcotics, by Law no 143 of July 26, 2000 with regard to the prevention and fight against the illicit traffic and consumption of narcotics. Article 3 of this Law stipulates that the bringing in and the taking out of the country, as well as the import and export of dangerous narcotics without a legal approval are punished with prison from 10-20 years and with the interdiction of certain rights. In paragraph 2 of the same article it is mentioned that whether the deeds enumerated in paragraph 1 refer to narcotics of a very high risk, the prison penalty is from 15-25 years and the interdiction of certain rights. The analysis of the infringement referring to the international traffic of narcotics is made in conformity with the structure mentioned in the doctrine and includes: the object and the subject of the infringement, the constitutive content: the objective aspect including the material element, the immediate consequence and the casualty connection; the subjective aspect of the infringement, as well as form and modalities of these infringements and the respective applicable sanctions.